Arka Chattopadhyay. Beckett, Lacan and the Mathematical Writing of the Real. Bloomsbury Academic, 2019. - Andrew J Kettler (Studies in 20th & 21st Century Literature, 2020)
Review of Arka Chattopadhyay. Beckett, Lacan and the Mathematical Writing of the Real. Bloomsbury Academic, 2019. 209 pp.
Keywords: Samuel Beckett; Jacques Lacan; mathematics